Foot-Drop Following Vertebroplasty: Case Report - Boran, Burak Orhan (Fırat University, 2006)
Objectives: Percutaneous vertebroplasty is a common and effective procedure in the treatment of compression fractures. In this paper, a patient presenting with foot-drop following vertebroplasty is presented. Case: A 71-year-old male patient was admitted with the complaints of radicular pain in the left leg and left foot-drop. His past medical history reveled that he had undergone vertebroplasty 3 months ago, due to L4 compression fracture. Computed tomography demonstrated polymethylmethacrylate leak and left L5 root compression. The patient was operated and the material was removed via left L5 hemilaminectomy and 1/3 medial facetectomy. Conclusion: Percutaneous vertebroplasty is a highly effective procedure in the treatment of compression fractures. On the other hand, polymethylmethacrylate leak is a common occurrence during the procedure. Because of the fact that, it rarely manifests any clinical signs, the condition is generally ignored. This case also indicates that, appropriate imaging should be performed, if radicular pain develops following vertebroplasty and surgery should be performed as indicated.©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Perkütan vertebroplasti, çökme kırıklarının tedavisinde yaygın olarak kullanılan son derece etkin bir yöntemdir Bu çalışmada, vertebroplasti sonrası kök basısı ve düşük ayak gelişen bir olgu sunulmuştur. Olgu: Yetmiş bir yaşında erkek hasta kliniğimize siyatalji tipinde ağrı ve sol ayakta kuvvetsizlik nedeniyle başvurdu. Yapılan nörolojik muayenesinde solda düşük ayak tespit edildi. Hastanın özgeçmişinden, 3 ay önce L4 çökme kırığı nedeniyle vertebroplasti yapıldığı öğrenildi. Bilgisayarlı tomografi tetkikinde, işlem esnasında polimetilmetakrilat sızıntısı olduğu ve bu nedenle sol L5 kök basısı geliştiği görüldü. Hasta bu nedenle operasyona alınarak, sol L5 hemilaminektomi ve 1/3 medyal fasetektomi yapıldı ve materyal ön epidural boşluktan çıkartıldı. Sonuç: Perkütan vertebroplasti çökme kırıklarının tedavisinde son derece etkili bir yöntemdir. Öte yandan, işlem esnasında, polimetilmetakrilat sızıntısı sık olarak görülmekte olup, nadiren klinik bulguya yol açtığı için yeterince önemsenmemektedir. Bu olgu da göstermektedir ki, vertebroplasti sonrası gelişen radiküler ağrılarda mutlaka uygun görüntüleme tetkikleri yapılmalı ve gerekli durumlarda, hasta ameliyat edilmelidir. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Vertebroplasti Sonrası Gelişen Düşük Ayak: Olgu Sunumu